Evidence of the enhanced negative thermal expansion in (1 − x)PbTiO3-xBi(Zn2/3Ta1/3)O3. Issue 5 (17th February 2020) - Yang, Tao; Lin, Kun; Li, Qiang; Wang, Yilin; Gu, Lin; Wang, Na; Deng, Jinxia; Chen, Jun; Xing, Xianran
Abstract : Enhanced polarization displacement in (1 − x )PbTiO3 - x Bi(Zn2/3 Ta1/3 )O3 solutions has been reported. Abstract : A series of new solid solutions, (1 − x )PbTiO3 - x Bi(Zn2/3 Ta1/3 )O3 (0 < x < 0.2), have been synthesized, which show abnormally enhanced negative thermal expansion. The results of synchrotron X-ray diffraction reveal that with the increase in the dopant of Bi(Zn2/3 Ta1/3 )O3 in the PbTiO3 system, the increase in spontaneous polarization displacement could improve the negative thermal expansion behavior due to the spontaneous volume ferroelectrostriction (SVFS) effect. The STEM images show that PbTiO3 -Bi(Zn2/3 Ta1/3 )O3 exhibits stronger polarization than PbTiO3, which reveals a greater deviation. Moreover, the STEM images show that the element Ta has larger spontaneous polarization displacement than other B-site atoms. Furthermore, density functional theory calculations confirm the enhancement of hybridization between the A-site cations and oxygen upon the introduction of Bi(Zn2/3 Ta1/3 )O3 . All the above pieces of evidence indicate that the interplay between the cations and oxygen plays a key role in the enhancement of negative thermal expansion.